2019
DOI: 10.1002/cphc.201801172
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Mannobioses Unravelled by Means of Raman Optical Activity

Abstract: Structural analysis of carbohydrates is a complicated endeavour, due to the complexity and diversity of the samples at hand. Herein, we apply a combined computational and experimental approach, employing molecular dynamics (MD) and density functional theory (DFT) calculations together with NMR and Raman optical activity (ROA) measurements, in the structural study of three mannobiose disaccharides, consisting of two mannoses with varying glycosidic linkages. The disaccharide structures make up the scaffold of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 65 publications
1
37
0
Order By: Relevance
“…We were able to recover most of the errors performing full optimization of the sugar while keeping the water molecules frozen (MM_w, i.e. the OPTSOLUTE approach used by the ''Manchester group'' 13,17 ), however, at additional computational cost. Further comparison of hybrid_w and hybrid_fo showed that excessive optimization without any restraints only worsens the results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We were able to recover most of the errors performing full optimization of the sugar while keeping the water molecules frozen (MM_w, i.e. the OPTSOLUTE approach used by the ''Manchester group'' 13,17 ), however, at additional computational cost. Further comparison of hybrid_w and hybrid_fo showed that excessive optimization without any restraints only worsens the results.…”
Section: Discussionmentioning
confidence: 99%
“…Small basis set 6-31G* was not able to accurately reproduce the spectral features. The widely used rDPS basis set 11,13,[17][18][19][20] (see Table S1 in the ESI †) provides significantly better results at a similar cost to the 6-31G* basis set. Using the 6-311++G** basis set provides further improvement of the results at B2.5Â the performance cost as compared to rDPS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique has been used to determine the secondary structure of native and carboxylated agarose gels . Recently, ROA has been applied to dimannosides with different glycosidic linkages …”
Section: Methods To Study Polysaccharide Conformations and Foldingmentioning
confidence: 99%